2008
DOI: 10.1152/advan.00063.2007
|View full text |Cite
|
Sign up to set email alerts
|

Learning approaches of undergraduate medical students to physiology in a non-PBL- and partially PBL-oriented curriculum

Abstract: Melaka Manipal Medical College (Manipal Campus; Manipal, Karnataka, India) conducts the Bachelor of Medicine and Bachelor of Surgery program, for which the admission intakes are during the months of March and September. The present study was undertaken to study the differences in learning approaches to physiology of undergraduate medical students in a partially problem-based learning (PBL)- and non-PBL-oriented curriculum. PBL was introduced as a curricular reform for the September 2006 batch of students (part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 17 publications
4
53
2
8
Order By: Relevance
“….097 a. Grouping Variable: PBL dan Non-PBL Mann-Whitney U Test results showed that there was no statistically significant difference in students' approach to learning in PBL and non-PBL groups (p-value = 0.097) ( Table 5). The results of this study are not the same as those obtained by Abraham et al (2008) found that students 'approach to learning in students with PBL approach differed significantly from students' approach to learning in students with non-PBL approach.…”
Section: Tabel 4 Frequency Distribution Of Respondents Based On Theircontrasting
confidence: 99%
See 2 more Smart Citations
“….097 a. Grouping Variable: PBL dan Non-PBL Mann-Whitney U Test results showed that there was no statistically significant difference in students' approach to learning in PBL and non-PBL groups (p-value = 0.097) ( Table 5). The results of this study are not the same as those obtained by Abraham et al (2008) found that students 'approach to learning in students with PBL approach differed significantly from students' approach to learning in students with non-PBL approach.…”
Section: Tabel 4 Frequency Distribution Of Respondents Based On Theircontrasting
confidence: 99%
“…Students who do so try to investigate the relationship between and integration of different parts of the lessons and their tasks. The findings of this study are congruent with the study of Abraham et al (2008), which states that scores of students who adopt deep approach to learning and strategic approaches to learning are significantly higher than non-PBL students. This finding is consistent with Mattick, Dennis and Bligh (2004) research, which shows that students achieve higher scores on the deep approach to learning from surface approach to learning.…”
Section: Tabel 4 Frequency Distribution Of Respondents Based On Theirsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been well known that integrated course teaching with PBL model had deeply shocked on our conventional medical education, the teaching in classroom respectively by the staff from different basic and clinical discipline, worldwide in the past several decades (i.e., Abraham, Vinod, Kamath, Asha, & Ramnarayan, 2008;Chen, Lai, Lu, Tsai, Chiang, Huang, & Yu, 2008;Fincham, & Shuler, 2001;Jones, McArdle, & O'Neill, 2002;Oda, Koizumi, 2008 The impact of medical education reform has unlimitedly touched the campus of Jinan University School of Medicine, in which the medical students have constantly been taught and trained as conventional teaching approach until several years ago. Therefore, the integrated courses were performed at Jinan University School of Medicine three years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Varios estudios han evaluado diferentes aspectos de los enfoques de aprendizaje en ingeniería, ciencias sociales y educación médica (7,(9)(10)(11) . Sin embargo, el enfoque de aprendizaje en las ciencias básicas en los estudiantes de medicina de primer año ha recibido poca atención, especialmente en los aspectos relacionados con el éxito académico, y la mayoría de los hallazgos son objeto de controversia.…”
Section: Introductionunclassified